The Application of Women Wearing Head Covering and Their Role in Ministry - Based on 1 Corinthians 11:3-6 and 14:34 (Asian Journal of Social Science Studies, 2017)
1 Corinthians 11:3-6 and 14:34, 35 are two of controversial passages in the New Testament. The present study was done to evaluate some issues. They are: (1) The meaning of “Headship?” (2) The meaning of “head-covering as a mark of subordination?” (3) Women’s role in the church or ministry? (4) The last, do women in Moslem countries or in non-Moslem Countries have to wear head coverings after they convert to Christianity? The results are: (1) Headship’s concept is the concept of love not oppression as God is head of Christ; Christ is head of man; man is head of woman in love’s perspective. The word “head” in “headship” means “source”; (2) Head coverings is a custom for Corinthians’ women, and it is a must in honoring their custom and to distinguish themselves from idolatrous women and prostitutes; (3) Women still have their roles in ministry. Women are a part of God’s ministry; (4) For Christians today, they may follow their customs as long as the customs are not against the word of God; or, if the custom is identical to a particular religion, then Christian must avoid it for it will cause misunderstanding for other people.